2010
DOI: 10.1007/s10567-010-0074-z
|View full text |Cite
|
Sign up to set email alerts
|

Problem Behavior in Children of Chronically Ill Parents: A Meta-Analysis

Abstract: The aim of this meta-analysis is to examine whether children of chronically ill parents differ from norm groups in problem behavior. We report moderator effects and overall effect sizes for internalizing, externalizing and total problem behavior assessed by children and parents. In fixed effect models, we found a significant overall effect size for internalizing problem behavior (number of studies k = 19, total sample size N = 1,858, Cohen’s d = .23, p < .01) and externalizing problem behavior (k = 13, N = 1,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
197
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(233 citation statements)
references
References 55 publications
22
197
4
3
Order By: Relevance
“…Their distress is likely due to their vulnerability and reliance on positive family functioning [8,9] and concerns about the parent's survival and the family's future [7]. Distress can lead to emotional and psychosocial problems [6], such as problematic internalization (e.g., depressive mood states) or externalization (e.g., aggression, delinquency) of behavior [9,10]. A child's age, gender, and cognitive maturity has been found to effect the way in which children respond to stressful situations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Their distress is likely due to their vulnerability and reliance on positive family functioning [8,9] and concerns about the parent's survival and the family's future [7]. Distress can lead to emotional and psychosocial problems [6], such as problematic internalization (e.g., depressive mood states) or externalization (e.g., aggression, delinquency) of behavior [9,10]. A child's age, gender, and cognitive maturity has been found to effect the way in which children respond to stressful situations [11].…”
Section: Introductionmentioning
confidence: 99%
“…So, feelings of chronic stress are indications of the impact of stressors and insufficient coping responses or resources on the child due to stressful circumstances during an extended period. These feelings may develop gradually, are unacknowledged or accepted as 'normal' by the child (Dufour et al 2006;Forehand et al 1998;Sieh et al 2010a;Verhaeghe et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We found that it made no difference which parent was ill, although another study found that mothers' health had a greater impact on young children's SDQ scores than fathers' health (Kelly and Bartley 2010). A recently published meta-analysis by Sieh et al (2010) also found that children of chronically ill parents had more problem behaviours than children of healthy parents, especially among girls and if the mother was ill. However, it was not possible to ascertain if parental gender had different effects for younger or older children.…”
Section: Discussionmentioning
confidence: 94%
“…Exploring intrapersonal changes in well-being in response to different stressors or events has long been a subject of research (Diener 2000 ;Clark et al 2001 ;Lucas et al 2003 ;Cronin de Chavez et al 2005 ;Lucas 2005 ;Luhmann and Eid 2009 ;Clarke and Georgellis 2010). More recently however researchers have begun to look at intrapersonal changes in SWB due to events experienced by others in their familial or social networks (Berg and Upchurch 2007 ;Fekete et al 2007 ;Giannakopoulos et al 2009 ;Pruchno et al 2009 ;Dorros et al 2010 ;Sieh et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation